2007
DOI: 10.1093/treephys/27.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Organ-dependent induction of systemic resistance and systemic susceptibility in Pinus nigra inoculated with Sphaeropsis sapinea and Diplodia scrobiculata

Abstract: Systemic induced resistance (SIR) is a well-known host defense mechanism against pathogen attack in herbaceous plants, but SIR has only recently been documented in conifers. We tested if inoculation of Austrian pine (Pinus nigra Arnold) with Sphaeropsis sapinea (Fr.:Fr.) Dyko and Sutton or Diplodia scrobiculata de Wet, Slippers and Wingfield results in SIR or systemic induced susceptibility (SIS) to subsequent colonization by S. sapinea. Induction at the stem base resulted in significant (P < 0.01) SIR in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 39 publications
7
95
0
Order By: Relevance
“…Induced resistance to dieback caused by Diplodia has also been demonstrated in pines [29], indicating that SAR might contribute to management of multiple disease problems. For practical reasons, substituting a chemical inducer of resistance for inoculation with a pathogen would be desirable, and the findings reported by Reglinski et al [30] and Fitza et al [31] suggest that chitosan merits consideration in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Induced resistance to dieback caused by Diplodia has also been demonstrated in pines [29], indicating that SAR might contribute to management of multiple disease problems. For practical reasons, substituting a chemical inducer of resistance for inoculation with a pathogen would be desirable, and the findings reported by Reglinski et al [30] and Fitza et al [31] suggest that chitosan merits consideration in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant changes in isorhapontigenin or stilbene glycosides concentrations were found. In a recent study, Blodgett et al (2007) found no correlation between the length of challenge lesions and PSME and concluded that stilbenes may not play a significant role in induced resistance against Sphaeropsis sapinea. Johansson et al (2004) compared the induced responses of Scots pine and Norway spruce after infection with the white rot fungi Heterobasidion annosum and Heterobasidion parviporum.…”
Section: Induced Phenolicsmentioning
confidence: 96%
“…Furthermore, pronounced accumulations of ester-and glycoside-bound benzoic acid derivatives were found in regions of infected branches that were not in contact with the pathogen, suggesting a systemic induction of phenylpropanoid metabolism (cf. Bonello et al 2006;Blodgett et al 2007). Evidence for the role of bark-associated phenolics in induced defense has also been gained from studies concerning polyphenolic parenchyma (PP) cells and conifer resistance (Franceschi et al 2000(Franceschi et al , 2005.…”
Section: Induced Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…They include both pre-and post-penetration mechanisms and can be categorized as constitutive or induced, chemical or mechanical, systemic or local (Bonello et al 2001;Bonello and Blodgett 2003;Luchi et al 2005;Gordon 2006;Eyles et al 2007;Gould et al 2008). Defence mechanisms are also categorized based on whether they produce qualitative or quantitative resistance (Heijari et al 2005;Bonello et al 2006;Hammerschmidt 2006;Blodgett et al 2007;Ganley et al 2008;Krokene et al 2008;Witzell and Martin 2008;Eyles et al 2010). It is important to stress that defence and resistance are not one and the same thing; defence mechanisms act against pathogens, but may or may not confer resistance, which is the ultimate outcome of the host-pathogen interaction.…”
Section: Resistance Mechanisms Involved In the Dothistroma-pinus Systmentioning
confidence: 99%